Navigating New Worlds: The College Transition of Rural Latinx Undergraduate Students from California’s San Joaquin Valley - Daniel Rios Arroyo (Journal of Research in Rural Education, 2025)
This study examined the college transition experiences of rural Latinx undergraduate students in California’s San Joaquin Valley. The literature on rural students in higher education is limited, and much of it has been focused on White students, especially those in areas such as Appalachia, the Midwest, and the Southern United States, which has led to the exclusion of rural Latinx undergraduate students and how their rurality intersects with their race to inform their higher education experiences. This study adds to the literature by focusing on the college transition experiences of rural Latinx undergraduate students from the San Joaquin Valley to better understand how race and rurality impact students’ experiences in higher education. Fifteen students engaged in two two-hour-long pláticas, which were conducted utilizing Chicana/Latina feminist pláticas (conversations), for a total of 30 pláticas. Three critical findings were revealed: (a) rural Latinx undergraduate students encounter academic challenges based on prior K–12 rural schooling, (b) they experienced racial microaggressions as they navigated unfamiliar racial dynamics on campus, (c) the rural Latinx undergraduate students felt socially disconnected from wealth and urban Latinx peers. These findings revealed the unique challenges that rural Latinx undergraduate students face in higher education.